Intervention to systematize fall risk assessment and prevention in older hospitalized adults: a mixed methods study - Johann Stuby; Pascal Leist; Noël Hauri; Sanjana Jeevanji; Marie Méan; Carole E. Aubert (BMC Geriatrics)
Abstract Background Fall-prevention interventions are efficient but resource-requiring and should target persons at higher risk of falls. We need to ensure that fall risk is systematically assessed in everyday practice. We conducted a quality improvement (QI) intervention to systematize fall risk assessment and prevention in older adults hospitalized on general internal medicine wards. We evaluated the efficacy of the intervention in a pre-post intervention study and assessed its feasibility and acceptability through a mixed methods process evaluation, which results are reported in here. Methods The QI intervention was conducted between 09/2022 and 10/2023 and targeted the nursing staff and residents in two tertiary hospitals of two different language and cultural regions of Switzerland. The intervention comprised an oral presentation, an e-learning, and reminder quizzes. We conducted a process evaluation including 25 interviews and a survey sent to all participants to assess feasibility and acceptability of the intervention. Quantitative data were analyzed descriptively and qualitative data with a mixed deductive and inductive approach. Results were integrated through meta-inferences. Results Among 544 clinicians, 59% completed the e-learning, 74% found the intervention useful, and 25% reported an increase in interprofessional team working. A rewarding system was deemed motivating by 33% of clinicians. Main implementation barrier was the high workload. A concise and clear content as well as regular reminders were perceived as facilitators. Conclusions A concise and multimodal QI intervention with regular reminders seemed to be feasible and well-accepted. Future QI intervention projects should consider the barriers and facilitators identified in this project to improve quality of care in older hospitalized adults. Trial registration The conducted research was not pre-registered.